Pneumoperitoneum without Intestinal Perforation in a Neonate: Case Report and Literature Review - Gummalla, Prabhavathi (Case Rep Pediatr, 2017)
Pneumoperitoneum in a preterm neonate usually indicates perforation of the intestine and is considered a surgical emergency. However, there are cases of pneumoperitoneum with no evidence of rupture of the intestine reported in the literature. We report a case of pneumoperitoneum with no intestinal perforation in a preterm neonate with respiratory distress syndrome who was on high frequency oscillatory ventilation (HFOV). He developed bilateral pulmonary interstitial emphysema with localized cystic lesion, likely localized pulmonary interstitial emphysema, and recurrent pneumothoraces. He was treated with dexamethasone to wean from the ventilator. Pneumoperitoneum developed in association with left sided pneumothorax following mechanical ventilation and cardiopulmonary resuscitation. Pneumoperitoneum resolved after the pneumothorax was resolved with chest tube drainage. He died from acute cardiorespiratory failure. At autopsy, there was no evidence of intestinal perforation. This case highlights the fact that pneumoperitoneum can develop secondary to pneumothorax and does not always indicate intestinal perforation or require exploratory laparotomy.